ATRACTIVO DEL FINANCIAMIENTO A LAS PEQUEÑAS MICROEMPRESAS PARA LA BANCA COMERCIAL PRIVADA - Copa, Tula (1996)
In Latin America, small and micro enterprises (SMEs) are considered a tool for combating poverty due to their high capacity to generate employment, in addition to being a significant source of GDP. This article seeks to demonstrate that SMEs, as a subject of credit, can be an attractive option for private commercial banks in Peru. For this purpose, two factors are examined: the Chilean experience of some years ago, since Peru presents the same conditions that made this possible in the neighboring country, and the analysis of the variables that affect the development of SME financing. It is shown that in 1992 the sector of financing to these companies shows great attractions for the financial sector, since there is an insufficient credit offer, the banking entities authorized to provide financing to SMEs are very few, the banks are increasing their money deposits. But at the same time there are risks, such as the arrival of large foreign banks in the market, the emergence of other credit institutions (edpymes) and a high risk of non-repayment of loans.